Contemporary coloproctology - Hartley, John E.; Hill, Jim; Scott, Nigel; Williams, J. Graham (Springer, 2012)
Contemporary Coloproctology covers colorectal surgery, as practiced today, in an easily accessible format with emphasis on bringing key facts rapidly into focus. It is ideal reading both for the medical trainee and the practicing colorectal surgeon. As well as a succinct presentation of the current colorectal knowledge base, each chapter contains practical advice and pearls of wisdom from established practicing clinicians.  A unique feature of the format is the identification of key references and questions and scenarios that present real life decisions in colorectal surgery.  Edited and authored by outstanding surgeons in their fields, this book brings the reader expertise in surgery and management across the various conditions encountered in coloproctology.